Sintesis dan Uji Aktivitas Tabir Surya C-Fenilkaliks [4] Resorsinaril Oktabenzoat - Budiana I Gusti M. Ngurah; Ni Nyoman Yuliani (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2019)
Research on the discovery of organic sunblock today continues to be intensively conducted because cases of skin cancer caused by sun exposure continue to increase from year to year. Recently, what is used to protect the skin from the dangers of sun exposure is a sunblock lotion product. This research aims to synthesize and test the new organic C-phenylcolics [4] resorcinaryl octabenzoat compound. This research is pure experimental research by testing sunblock activity using Ultraviolet-Visible Spectrophotometry. The C-phenylcallic [4] resorcinaryl octabenzoate compound was synthesized by the C-phenylcalcid [4] resorcinarene method with benzoyl chloride using a catalyst and pyridine solvent. Characterization of reaction products used infra-red spectrometers and proton-NMR. Meanwhile, testing sunblock activity was conducted in vitro using the ultraviolet spectrometry method. The synthesis results showed that C-phenylcalcid [4] resorcinyl octabenzoat was in the form of a dark yellow solid, melting point of 238-240 oC and yield of 74.10%. The in vitro test results showed that C-methylcolics [4] resorcinyl octabenzoat has a broad spectrum because it can absorb UV B and UV C rays with an SPF value of 30. This compound has the potential to be developed as a sunblock.